Prophetic Leadership Model for Public Bureaucracy: How it’s Works? - M. Ridho Syabibi (JURNAL ILMIAH SYI'AR, 2022)
This study discusses prophetic leadership models and how to facilitate them in the public bureaucracy. Prophetic leadership is the ability possessed by leaders to influence subordinates following Islamic demands (leading to the pattern of the leadership of Rasulullah PBUH). Systematically we work. Starting with searching for sources of reading (al-Qur'an, hadith, journals, and books), then reading interactive, making reading tables, and reducing the essence of reading before being transferred to the worksheet. This study found that leadership can be explained through extrinsic and intrinsic motivation theories. Prophetic leadership belongs to innate leadership because it uses spirituality as the basis of value. In Islam, prophetic leadership not only stems from intrinsic or ethical motivation but also combines divine-world motivation (Hashanah) and Akhirah. Then it is known that the triggers of prophetic leadership can result from imitating the Prophet Muhammad and social experience. The process of its formation took place for a long time, so it is concluded that prophetic leadership can be applied in the public bureaucracy if the state civil apparatus of the country has religious maturity. Efforts to realize prophetic leadership can begin by analyzing the level of religious maturity. Bringing spiritual nuances within the organization is considered to be sufficient to facilitate the ASN of a mature country. We are just at the analytical stage and predict its application opportunities. The next researcher needs to raise the best practice case from this model and formulate a measuring tool to assess the successful application of prophetic leadership in the public bureaucracy.